RON RECEPTOR TYROSINE KINASE DEPENDENT HEPATIC NEUTROPHIL RECRUITMENT AND SURVIVAL BENEFIT IN A MURINE MODEL OF BACTERIAL PERITONITIS - Caldwell, Charles C. (2008)
OBJECTIVE: To determine if Ron receptor tyrosine kinase signaling impacts the in vivo response to bacterial peritonitis. DESIGN, SETTING AND SUBJECTS: A genetic approach comparing wild type mice to mice with a targeted deletion of the Ron tyrosine kinase signaling domain (TK(−/−)) was undertaken to determine the influence of Ron receptor in the in vivo response to a well-characterized model of bacterial peritonitis and sepsis induced by cecal ligation and puncture (CLP). MEASUREMENTS: Several clinical (ie. survival curves, blood and tissue bacterial burdens, and neutrophil oxidative burst), morphologic (ie. liver histology and leukocyte trafficking) and biochemical parameters (ie. serum aminotransferases and select serum cytokine and chemokine levels) important for assessing inflammatory responses to bacterial infection were assessed in mice following CLP. MAIN RESULTS: Ron TK(−/−) mice had a significant decrease in survival time compared to controls, and this was associated with a significant increase in bacterial colony forming units found in the blood and several end-organs. Moreover, this increased bacterial load was associated with increased liver necrosis and serum alanine aminotransferase levels. Neutrophils isolated from TK(−/−) mice exhibited decreased spontaneous oxidative burst capacity ex vivo, and by intravital microscopy, a reduced level of neutrophil migration to and translocation within the liver was observed. Loss of Ron signaling resulted in significantly reduced production of serum MCP-1 and IL-6 levels following CLP, and peritoneal macrophage isolated from TK(−/−) mice exhibited blunted production of MCP-1, IL-6 and MIP-2 following stimulation with endotoxin ex vivo. CONCLUSION: Ron signaling negatively regulates the response to polymicrobial infection by regulating the activation and recruitment of inflammatory cells necessary for clearing a systemic bacterial burden. This effect may be regulated in part through the Ron-dependent, macrophage-mediated, production of cytokines and chemokines, namely MCP-1, IL-6 and MIP-2, important for neutrophil mobilization.